Purifying magnetic bead, preparation method thereof and application of purifying magnetic bead in grain heavy metal detection

By developing a purified magnetic bead that grafts polyamino adsorption groups on the shell, the signal masking and matrix interference problems in arsenic detection in rice are solved, and the accurate detection and detection process of arsenic is achieved.

CN119386839APending Publication Date: 2025-02-07ACAD OF NAT FOOD & STRATEGIC RESERVES ADMINISTRATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411431249.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art has difficulty in detecting arsenic in the detection of heavy metals in grains, especially when arsenic and copper coexist in rice samples, the electrochemical signal of copper is similar to that of arsenic, resulting in signal masking; at the same time, the grain matrix has severe interference, affecting the detection accuracy.

Method used

A purified magnetic bead is developed that uses magnetic Fe3O4 particles as the core, forms an epoxy-encapsulated shell through polymerization, and uniformly grafts the polyamino adsorption groups on the shell. The magnetic beads can achieve strong adsorption of copper and weak adsorption of arsenic by selecting the type and amount of amino functional compounds, eliminate the masking effect of copper on arsenic, and remove the interference effect of the matrix in rice.

Benefits of technology

It significantly improves the electrochemical detection accuracy of arsenic in rice, ensures that the arsenic content is basically undamaged, and simplifies the purification process and improves the accuracy and sensitivity of the detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a purification magnetic bead, a preparation method thereof and application of the purification magnetic bead in grain heavy metal detection. According to the purification magnetic bead, magnetic Fe3O4 particles serve as an inner core, a shell wrapped by an epoxy group is formed through a polymerization reaction, and a multi-amino adsorption group is further evenly grafted to the shell; wherein the multi-amino adsorption group is formed by constructing an amino functional compound, and the amino functional compound is selected from one or more of triethylenetetramine, hexamethylenediamine and a polyethyleneimine oligomer with the molecular weight of 1000 or below. The purification magnetic bead provided by the invention has excellent adsorption performance on metal ions and a rice matrix in rice, especially has relatively high adsorption performance on copper ions, and has relatively weak adsorption capacity on As, so that in the application of electrochemical detection of the arsenic content in grains, the masking effect of copper on arsenic and the interference effect of the matrix can be effectively reduced, and the detection accuracy is improved. The arsenic detection accuracy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adsorption materials, and specifically comprises a purification magnetic bead and a preparation method thereof and application thereof in grain heavy metal detection. Background Art

[0002] Electrochemical rapid detection technology provides a fast, cheap and portable method for the detection of heavy metals in grains. It is an economical and timely method that can fit my country's national conditions and implement rapid detection of grains at the storage site. However, there are many difficulties in the detection of arsenic. First, arsenic and copper often coexist in rice samples. The content of copper is usually dozens or even hundreds of times that of arsenic. At the same time, the electrochemical signal of copper is similar to that of arsenic, which has a masking effect on the signal of arsenic. Secondly, there are a large number of complex grain matrices in the sample to be tested, such as protein, fat, polysaccharide, salt, etc., especially in the process of arsenic extraction, heating, ultrasound, acid extraction and other means are used. A large amount of grain matrix is ​​also dissolved in the sample solution to be tested, thereby interfering with the signal in the detection and affecting the detection accuracy. Therefore, designing and developing a technology and new materials that can be used to purify interfering substances is an effective means to improve the accuracy of rice arsenic detection.

[0003] Magnetic adsorption materials have strong adsorption capacity, and can be quickly and easily separated from solid / liquid phases using external magnetic fields, and can be applied to the fields of rapid detection and automation technology. CN110411812A discloses a carboxyl magnetic bead for enriching and purifying lead and cadmium in food. The magnetic bead can adsorb lead, cadmium and a certain amount of other ions in the sample, but does not have a strong adsorption effect on the food matrix. Therefore, after strong acid elution, the organic matrix is ​​rarely present in the eluent because it is not adsorbed in large quantities, but the interfering ions with similar physical properties to lead and cadmium are eluted together with the adsorption of the carboxyl magnetic beads and cannot be purified, and still have a certain interference effect on the detection. CN115090274B discloses a method for preparing a magnetic branched polyethyleneimine for treating copper ions in sewage. The method uses N-hydroxysuccinimide as a grafting agent, and polyethyleneimine is added under the action of a dehydrating agent to generate amides. The prepared magnetic beads have a good adsorption effect on copper ions in wastewater, but the magnetic beads are poor in stability in acidic and alkaline solutions because they are connected by amide bonds. CN112457456B discloses a preparation method of a polystyrene-divinylbenzene modified magnetic carbon nanotube composite material and its application in pesticide residue detection. The material is a new QuEChERS adsorbent that can purify matrix interference in fruit and vegetable samples, thereby improving the detection accuracy and sensitivity of pesticide residues. However, the preparation method of the adsorbent is relatively complicated and cumbersome, the price of carbon nanotubes is relatively expensive, and it is not clear whether it can be used to purify food matrices. The applicant's team has previously developed a magnetic polymer composite material m-P6 (CN116371378B), which can simultaneously adsorb four heavy metals, lead, cadmium, arsenic, and mercury, as well as food matrices, and elute heavy metals with eluent E12, but E12 will not have an elution effect on the food matrix, so it can achieve the effect of enriching and purifying heavy metals in food. However, it is well known that arsenic is difficult to be adsorbed due to its strong mobility. In the field of adsorption materials, the research on arsenic adsorption has always been a difficult problem that has attracted extensive attention from scientific and technological workers. The adsorption principle of m-P6 developed by the applicant on arsenic is a single electron transfer catalytic oxidation in a synergistic adsorption process, which converts trivalent arsenic into pentavalent arsenic and then conducts adsorption. However, in the electrochemical detection of arsenic, trivalent arsenic with redox signals is usually detected, so the idea of ​​catalytic oxidation to pentavalent arsenic is not feasible here. Summary of the invention

[0004] In view of the above problems existing in the prior art, the first object of the present invention is to provide a purification magnetic bead.

[0005] The second object of the present invention is to provide a method for preparing the purification magnetic beads as described above.

[0006] The third object of the present invention is to provide an application of the purification magnetic beads as described above in the detection of heavy metals in grains.

[0007] The fourth object of the present invention is to provide a method for electrochemically detecting arsenic content in rice.

[0008] To achieve the above first object, the technical solution adopted by the present invention includes:

[0009] The present invention discloses a purification magnetic bead, wherein the purification magnetic bead has a magnetic Fe3O4 particle as a core, forms an epoxy-wrapped shell by polymerization reaction, and has multiple amino adsorption groups uniformly grafted on the shell;

[0010] The polyamino adsorption groups are formed by constructing amino functional compounds, and the amino functional compounds are selected from one or more of triethylenetetramine, hexamethylenediamine, and polyethyleneimine oligomers with a molecular weight of less than 1000.

[0011] Based on the many problems with the current electrochemical detection of arsenic content in grains, the applicant team changed the strategy to remove interfering impurities while retaining the arsenic intact. The most interfering substances in the electrochemical detection of arsenic are copper ions (copper masking effect) and the matrix in rice (matrix interference effect). At the same time, it is considered that the process of removing interfering impurities is easier to operate and saves time than adsorption and then elution. Therefore, after the interfering impurities are determined, a purification magnetic bead with mild reaction conditions, low cost, simple operation, and high efficiency in adsorbing metal ions such as copper in rice and rice matrix is ​​developed. It has considerable application value for the electrochemical detection of arsenic in rice, and it also opens up new ideas for improving the accuracy and sensitivity of rapid detection technology of trace heavy metals in grains.

[0012] In the present invention, commercially available or homemade Fe3O4 particles are selected as the magnetic core, and a coating shell composed of a polymer and a polyamino modification layer grafted on the shell are sequentially formed on the surface through two reactions. The coating shell is designed to fully wrap the Fe3O4 particles and firmly fix the grafted amino functional compounds to prevent the amino functional compounds from falling off during the adsorption process to affect the adsorption effect. The polyamino modification layer constructed with amino functional compounds mainly adsorbs various interfering impurities in the system, such as metal ions (Cu, etc.) and matrix (protein, fat, etc.). It should be particularly noted that the present invention can achieve strong adsorption of Cu and weak adsorption of As by selecting the type and amount of amino functional compounds, so that the adsorption rate of As by the purification magnetic beads is maintained below 5%, or even below 3%, and the adsorption capacity of the surface of the purification magnetic beads is basically consistent, thereby eliminating the masking effect of copper on arsenic and basically not damaging the arsenic content. In addition, the purification magnetic beads can also eliminate the interference effect of the matrix in rice, so that the detection accuracy of arsenic can be significantly improved.

[0013] Furthermore, the shell is a polymer layer obtained by cross-linking polymerization of monomers, additives and cross-linking agents under the action of an initiator.

[0014] Furthermore, the monomer is selected from glycidyl methacrylate (GMA), the additive is selected from polyvinyl pyrrolidone (PVP K-30), the cross-linking agent is selected from ethylene glycol dimethacrylate (EDMA), and the initiator is selected from one or more of azobisisobutyronitrile (AIBN), dimethyl azobisisobutyrate, ammonium persulfate, potassium persulfate, benzoyl peroxide and tert-butyl benzoyl peroxide.

[0015] Further, the molar ratio of glycidyl methacrylate, polyvinyl pyrrolidone, Fe3O4 particles and ethylene glycol dimethacrylate is 1:0.4:0.2-1:0.12-0.2; illustratively, the molar ratio can also be 1:0.4:0.2-0.5:0.12-0.2, 1:0.4:0.2-0.8:0.12-0.2, 1:0.4:0.5-1:0.12-0.2, 1:0.4:0.5-0.8: 0.12-0.2, 1: 0.4: 0.8-1: 0.12-0.2, 1: 0.4: 0.2-0.5: 0.15-0.2, 1: 0.4: 0.2-0.8: 0.15-0.2, 1: 0.4: 0.5-1: 0.15-0.2, 1: 0.4: 0.5-0.8: 0.15-0.2, 1: 0.4: 0.8-1: 0.15-0.2, 1: 0.4: 0.2-1: 0.15-0.2, etc.;

[0016] The molar ratio of glycidyl methacrylate to azobisisobutyronitrile is 20-50:1.

[0017] To achieve the above second purpose, the technical solution adopted by the present invention includes:

[0018] The present invention discloses a method for preparing the purification magnetic beads as described above, comprising the following steps:

[0019] In a protective atmosphere, monomers, additives, crosslinking agents and Fe3O4 particles are mixed and crosslinked and polymerized under the action of an initiator. After the reaction is completed, the magnetic microspheres are washed and dried to obtain magnetic microspheres.

[0020] The amino functional compound solution is added to the magnetic microspheres, and the reaction is carried out at 60-80° C. for 6-24 hours to obtain the purification magnetic beads.

[0021] Further, the concentration of the amino functional compound solution is 1-100wt%. Exemplarily, the concentration of the amino functional compound solution can be 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 100wt%, etc. If the concentration of the amino functional compound solution is too low, the amount of amino groups on the multi-amino modified layer will be too small, which is not conducive to the adsorption of metal ions and substrates. If the concentration of the amino functional compound solution is too large, the ability of the purification magnetic beads to adsorb ions is close to equilibrium, and the adsorption effect does not change much. In a specific embodiment, when the concentration of the amino functional compound solution is 40-70wt%, the adsorption effect is better. The dispersing solvent used when dispersing the amino functional compound is selected from one of water, a mixed solution of ethanol and water, tetrahydrofuran, and N,N-dimethylformamide.

[0022] Furthermore, a certain amount of solvent, such as THF, etc., can be added during the preparation of the magnetic microspheres.

[0023] Furthermore, the reaction temperature of the cross-linking polymerization reaction is 60-80° C., and the reaction time is 6-24 h.

[0024] Furthermore, the protective atmosphere refers to a nitrogen atmosphere or an argon atmosphere.

[0025] To achieve the third objective above, the technical solution adopted by the present invention includes:

[0026] The present invention discloses an application of the purification magnetic beads described above in the detection of heavy metals in grains.

[0027] To achieve the fourth objective above, the technical solution adopted by the present invention includes:

[0028] The present invention discloses a method for electrochemically detecting the arsenic content in rice, wherein the purification magnetic beads described above are used to adsorb metal ions and food matrix in a rice extract to purify the rice extract, the purification magnetic beads are fixed with an external magnetic field, the supernatant is taken, and the arsenic content in the purified rice extract is detected;

[0029] The metal ions are selected from at least one of Cu, Cd, Pb, Al, V, Cr, Co, Ni, Zn, Ga, Se, Ag, In, and U.

[0030] Before being mixed with the rice extract, the purification magnetic beads are generally dispersed in a solvent at a concentration of 20-100 mg / mL; preferably 40-60 mg / mL.

[0031] Furthermore, the solid-liquid ratio of the purification magnetic beads to the rice extract is 1-5 mg / mL, preferably 5 mg / mL.

[0032] Furthermore, the specific steps of the electrochemical detection method of arsenic content in rice are:

[0033] Adding an appropriate amount of reducing agent and dilute nitric acid to a rice sample and subjecting the sample to heating and microwave treatment to obtain a rice extract to be tested, neutralizing the rice extract with a sodium hydroxide solution to a pH value in the range of 3-5, and setting aside;

[0034] The purification magnetic beads are added to the rice extract in proportion and shaken for 1-5 minutes, preferably 1 minute. The purification magnetic beads are fixed with an external magnetic field, and the supernatant is taken. Then, the modified working electrode is used to test by anodic stripping voltammetry to obtain the electrochemical detection result. In addition, the obtained electrochemical detection result can be compared with the test results of the rice extract in ICP-MS and / or AFS to calculate the recovery rate.

[0035] Beneficial effects of the present invention:

[0036] The invention obtains a novel purification magnetic bead by sequentially forming a coating shell composed of a polymer and a polyamino modified layer grafted on the shell on Fe3O4 particles. By selecting the amino functional compound constituting the polyamino modified layer and selecting the polymerization monomer and the crosslinking agent for the coating shell, the amino functional compound on the obtained purification magnetic bead is firmly fixed on the coating shell, and more importantly, it can have a good adsorption effect on interfering impurities (metal ions such as Cu and matrices such as protein and fat) in rice, especially has good adsorption performance for copper ions that have a masking effect on arsenic in electrochemical detection, while maintaining weak adsorption of arsenic (the adsorption rate of As is maintained below 5%, or even below 3%), reducing the masking effect and matrix effect of the test solution, thereby improving the accuracy of detection. In particular, when the amino functional compound is triethylenetetramine, the adsorption rate of the purification magnetic bead to Cu is 100.0%, and As is not adsorbed, showing a strong advantage in the application of electrochemical detection of arsenic in rice.

[0037] The purification magnetic bead preparation method provided by the present invention has simple synthesis steps, mild reaction conditions, low cost, and is easy to promote and apply.

[0038] The purification magnetic beads provided by the present invention are suitable for the detection of arsenic content in rice, and are particularly suitable for the electrochemical rapid detection of arsenic in rice. They can quickly adsorb copper ions with masking signals and rice matrix in rice samples to be tested, but have no obvious effect on arsenic, thereby purifying the samples to be tested, making their components to be tested more single, and improving the accuracy and sensitivity of detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The Fourier transform infrared spectrum of the purified magnetic beads prepared in Example 2 of the present invention is shown.

[0040] Figure 2 The electron scanning microscope morphology image of the purification magnetic beads prepared in Example 2 of the present invention is shown.

[0041] Figure 3 The magnetic performance curve of the purification magnetic beads prepared in Example 2 of the present invention is shown.

[0042] Figure 4 The figure shows the experimental results of the multi-metal ion adsorption experiment of Experimental Example 1 of the present invention.

[0043] Figure 5 The adsorption performance diagram of the purification magnetic beads prepared in Example 5 of the present invention at different TETA solution concentrations is shown.

[0044] Figure 6 The application of m-PGMA-TETA50 prepared by the present invention in electrochemical detection is shown.

[0045] Figure 7 The application of m-PGMA-TETA50 prepared by the present invention in reducing the matrix effect of rice is shown. DETAILED DESCRIPTION

[0046] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] To further illustrate the technical means and effects of the present invention, the method of the present invention is further described in detail below through specific examples, but the present invention is not limited thereto. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and consumables described are commercially available unless otherwise specified.

[0048] Example 1

[0049] Weigh GMA (5 g), PVP K-30 (1.5 g), Fe3O4 (6 g), and EDMA (0.8 mL) and place them in a two-necked bottle, fill it with argon, add 100-150 mL of THF solvent, dissolve the initiator AIBN (0.11 g) in THF, inject it into the reaction bottle under argon protection, heat to 60 ° C, stir at 500 rpm for 12 hours, stop heating after the reaction is completed, and separate the magnetic microspheres under the action of an external magnetic field after returning to room temperature, wash them three times with deionized water, and obtain regular-shaped magnetic microspheres m-PGMA after freeze-drying.

[0050] Comparative Example 1

[0051] The preparation method is the same as that of Example 1, except that the amount of Fe3O4 used is changed to 1.6 g. It is found that the polymer in the obtained reaction product is excessive, and a large amount of products with weak or no magnetic attraction are found in the magnetic separation process, which cannot be used in subsequent experiments.

[0052] Comparative Example 2

[0053] The preparation method is the same as that in Example 1, except that the amount of EDMA used is changed to 1.4 mL. It is found that the reaction product obtained has an uneven shape and weaker magnetic adsorption performance than that in Example 1, and cannot be used in subsequent experiments.

[0054] Comparative Example 3

[0055] The preparation method is the same as that of Example 1, except that the amount of initiator AIBN is changed to 0.28 g. It is found that the obtained reaction product is not a microsphere with regular shape, which easily causes uneven magnetic properties on the surface of the magnetic microsphere.

[0056] Comparative Example 4

[0057] The preparation method is the same as that of Example 1, except that the added solvent is changed to a mixed solvent of ethanol and water (9:1, v / v). It is found that the obtained reaction product is not a microsphere with regular shape, which easily causes uneven magnetic properties on the surface of the magnetic microspheres.

[0058] Example 2

[0059] 0.5 g of the magnetic microsphere m-PGMA prepared in Example 1 and 50 wt% TETA (triethylenetetramine) solution were added to a reaction bottle, and DMF was used as a dispersing solvent to make the reaction system to 5 mL. After sufficient stirring, the temperature was raised to 80°C and the reaction was carried out for 12 h. After the reaction, the mixture was poured into water and washed three times. After magnetic separation, the product m-PGMA-TETA50 was obtained by freeze-drying. The amino content of m-PGMA-TETA50 was 5.16 mmol / g.

[0060] Figure 1 It can be clearly seen in the FT-IR image that after the reaction, 910 cm -1 and 851cm -1 The characteristic peak of epoxy group at 1632cm disappeared, indicating that the reactants have been ring-opened and reacted with amino groups. -1 The newly added peak at 3500cm is the characteristic peak of NH on ring-opening grafting. -1 The enhancement of the peak at is the characteristic peak of OH generated after the epoxy ring opening and the grafted NH.

[0061] Figure 2It can be seen from the SEM image that the synthesized m-PGMA-TETA50 still retains the microspherical shape, and the surface of the microspheres is attached with dense particles and is uneven.

[0062] Magnetic adsorption performance Figure 3 As shown in the figure, compared with the magnetic properties of Fe3O4, the synthesized m-PGMA-TETA50 has a decreased magnetic property due to the epoxy and amino functional compounds wrapped in the outer layer, but still maintains good paramagnetism, so solid-liquid separation can be completed within 5 seconds.

[0063] Example 3

[0064] 0.5 g of the magnetic microsphere m-PGMA prepared in Example 1 and 50 wt% DAH (hexamethylenediamine) solution were added to a reaction bottle, and DMF was used as a dispersing solvent to make the reaction system to 5 mL. After sufficient stirring, the temperature was raised to 80°C and the reaction was carried out for 12 h. After the reaction, the mixture was poured into water and washed three times. After magnetic separation, the product m-PGMA-DAH50 was obtained by freeze-drying. The amino content of m-PGMA-DAH50 was 3.46 mmol / g.

[0065] Example 4

[0066] 0.5 g of the magnetic microsphere m-PGMA prepared in Example 1 and 50 wt% PEI (polyethyleneimine) (MW 600) solution were added to a reaction bottle, and DMF was used as a dispersing solvent to make the reaction system to 5 mL. After sufficient stirring, the temperature was raised to 80°C and the reaction was carried out for 12 h. After the reaction, the mixture was poured into water and washed three times. After magnetic separation, the product m-PGMA-PEI50 was obtained by freeze-drying. The amino content of m-PGMA-PEI50 was found to be 4.08 mmol / g.

[0067] Comparative Example 5

[0068] 0.5 g of the magnetic microsphere m-PGMA prepared in Example 1 and 50 wt% PEI (MW 1800) solution were added to a reaction bottle, and DMF was used as a dispersing solvent to make the reaction system to 5 mL. After sufficient stirring, the temperature was raised to 80° C. and the reaction was carried out for 12 h. After the reaction, the product was poured into water and washed three times. After magnetic separation and freeze-dried, the product was obtained. After testing, the amino content was 4.26 mmol / g.

[0069] Comparative Example 6

[0070] 0.5 g of the magnetic microsphere m-PGMA prepared in Example 1 and 50 wt% MA (melamine) solution were added to a reaction bottle, and DMF was used as a dispersing solvent to make the reaction system to 5 mL. After sufficient stirring, the temperature was raised to 80° C. and the reaction was carried out for 12 h. After the reaction, the mixture was poured into water and washed three times. The product was obtained by magnetic separation and freeze-drying. The amino content was found to be 2.14 mmol / g.

[0071] Test Example 1: Multi-metal ion adsorption experiment

[0072] GBW(E)082429, a mixed standard substance containing 29 elements, was prepared into a standard substance solution with a concentration of 250 μg / L for adsorption experiments on elements such as Cu and As.

[0073] It should be noted here that since the main research object of the inventor's unit is grain, oil and food, the application purpose of the present invention is to purify interfering ions and rice matrix in the rapid detection of rice arsenic. Therefore, the selected standard substances and prepared concentrations are to meet the industry needs of grain, oil and food testing. In addition, since substances containing Na, K, Fe, etc. are required in the sample preparation process, the results of these three ions are not included in the statistics.

[0074] Weigh 100 mg of m-PGMA-TETA50 prepared in Example 2 and place it in a centrifuge tube, add 2 mL of 20% ethanol solution, the concentration of the m-PGMA-TETA50 magnetic bead solution is 50 mg / mL, add the above-mentioned standard substance solution as A solution to the rice blank solution after dilute acid extraction, take 0.5 mL of A solution into a centrifuge tube, add 0.4 mL of 4% sodium hydroxide solution to neutralize it, so that the pH of the system is within the range of 3-5, add 0.1 mL of m-PGMA-TETA50 magnetic bead solution, use a vortex vibrator to vortex at 2500 rpm for 1 min, fix the magnetic beads with an external magnetic field, take 0.1 mL of the supernatant and add it to 5% (v / v) dilute nitric acid to a volume of 5 mL, prepare the test solution B solution for ICP-MS detection, and measure the concentration of each ion in B solution. The adsorption rate = (C0-C B ) / C0, C0 is the concentration of the prepared standard solution A after dilution 100 times, C B The residual concentration of each metal is measured in liquid B. The purification magnetic beads of other embodiments and comparative examples were tested for performance by referring to the above process.

[0075] Results Figure 4, see Table 1 for some experimental data. In the multi-metal ion adsorption experiment, the purification magnetic beads prepared in Example 2 have good adsorption performance for Cu, Cd, Pb, Al, V, Cr, Co, Ni, Zn, Ga, Se, Ag, In, and U, with an adsorption rate of 100.0% for Cu, and no adsorption for As, so it can be used as a material for purifying interfering ions in the electrochemical detection of rice arsenic. The purification magnetic beads prepared in Example 3 also have certain adsorption performance for multiple ions, but the adsorption capacity is not as good as that of m-PGMA-TETA50 in Example 2, among which the adsorption rate for Cu is 57.2%, and the adsorption rate for As is 2.5%. If the concentration of the magnetic bead solution is further increased to 100 mg / mL, the adsorption rate for Cu can reach more than 90%, and the adsorption performance of As is still maintained below 5%, indicating that it can be used as a material for purifying interfering ions. The purification magnetic beads prepared in Example 4 also have certain adsorption properties for multiple ions, but the adsorption capacity is not as good as the m-PGMA-TETA50 in Example 2, wherein the adsorption rate for Cu is 82.0%, and the adsorption rate for As is 0.9%. If the concentration of the magnetic bead solution is further increased to 100 mg / mL, the adsorption rate for Cu can reach more than 99%, and the adsorption performance of As is still maintained below 3%, indicating that it can be used as a material for purifying interfering ions. The purification magnetic beads prepared in Comparative Example 5 also have certain adsorption properties for multiple metal ions, but the adsorption capacity is not as good as the m-PGMA-TETA50 in Example 2, wherein the adsorption rate for Cu is 62.9%, and the adsorption rate for As is 16.8%. The adsorption rate for As is too large, and it is not suitable for use as a purification material in the electrochemical detection of arsenic in rice. The adsorption capacity of the purification magnetic beads prepared in Comparative Example 6 for multiple ions failed to reach 50%, wherein the adsorption rate for Cu was 5.8%, and the adsorption rate for As was 8.9%, which is not suitable for use as a purification material in the electrochemical detection of arsenic in rice.

[0076] Table 1 Summary of adsorption rates of various purification magnetic beads

[0077]

[0078]

[0079] From the comparison of the results of Examples 2-4 and Comparative Examples 5-6, it can be seen that the purification magnetic beads prepared by using TETA as the amino functional compound have the best adsorption performance for interfering ions and the dosage is relatively small. Therefore, TETA is used as the amino functional compound to further discuss the effect of the amino content on the purification magnetic beads on the adsorption performance.

[0080] Example 5

[0081] Based on the preparation process of Example 2, the concentration of the TETA solution was adjusted between 1 and 70 wt%. Specifically, the adsorption performance of different purification magnetic beads (i.e., m-PGMA-TETA1, m-PGMA-TETA5, m-PGMA-TETA10, m-PGMA-TETA20, m-PGMA-TETA30, m-PGMA-TETA40, m-PGMA-TETA50, m-PGMA-TETA60, and m-PGMA-TETA70) prepared at 1 wt% (0.39), 5 wt% (1.25), 10 wt% (1.64), 20 wt% (2.34), 30 wt% (3.13), 40 wt% (4.47), 50 wt% (5.16), 60 wt% (5.92), and 70 wt% (6.08) was evaluated by referring to the method of Experimental Example 1. The results are shown in Figure 5 , some experimental data are shown in Table 2. As the concentration of TETA solution increases, the adsorption performance of purification magnetic beads for multi-metal ions gradually increases, while there is no obvious adsorption effect on arsenic ions. When the concentration of TETA solution reaches 50%, the ability of magnetic beads to adsorb ions is close to equilibrium. Considering the dosage of magnetic beads and adsorption performance, m-PGMA-TETA50 is the best choice.

[0082] Table 2 Summary of adsorption rates of various purification magnetic beads

[0083]

[0084] Example 6

[0085] The m-PGMA-TETA50 of Example 2 was used for electrochemical detection in the presence of arsenic and copper. Figure 6 As shown in A, Cu has a masking effect on the detection of As in electrochemical detection. If copper ions are present, the concentration of arsenic cannot be accurately determined. Based on this, an arsenic-copper rice extract spiked solution was prepared (As concentration was 1-100 ppb, and 200 ppb of copper ions were mixed into each sample), 0.5 mL of sample solution was taken into a centrifuge tube, and the arsenic-copper rice extract spiked solution was neutralized with 0.4 mL of 4 wt% sodium hydroxide solution to a pH range of 3-5. Then, 0.1 mL of m-PGMA-TETA50 magnetic bead solution with a concentration of 50 mg / mL was added to the arsenic-copper rice extract spiked solution and shaken for 1 min. After fixing the magnetic beads with an external magnetic field, 0.2 mL of the supernatant was taken and added to the bottom solution, and then the modified working electrode was used for testing by anodic stripping voltammetry. The results are shown in FIG. Figure 6 As shown in B, Cu in the mixed solution can be purified by m-PGMA-TETA50, making As show a good linear relationship.

[0086] Example 7

[0087] The purification effect of m-PGMA-TETA50 on rice matrix in Example 2 was investigated. 500 mg of rice blank sample was weighed, 10 mL of 5% nitric acid solution was added for extraction, and a vortex vibrator was used to vortex at 2500 rpm for 30 min and then centrifuged to obtain an extract containing rice matrix. The standard solution of 1-100 ppb As was added to the rice matrix extract in sequence to obtain a spiked extract containing rice matrix (liquid C). According to the above method, 0.5 mL of solution C was prepared again, and then 0.4 mL of 4 wt% sodium hydroxide solution was used to neutralize solution C to a pH range of 3-5. Then, 0.1 mL of 50 mg / mL m-PGMA-TETA50 magnetic bead solution was added to each solution C and shaken for 1 min. After the magnetic beads were fixed with an external magnetic field, the purified solution was poured out to obtain the magnetic bead purified solution (liquid D) after purifying the rice matrix. Subsequently, the standard solution of As (1-100 ppb), the extract containing the rice matrix (liquid C), and the magnetic bead purified solution (liquid D) were all added with quantitative detection acid, and the As content in the above three solutions was detected by EC and AFS, respectively, so as to compare the influence of the matrix effect on the accuracy of the As content. Results Figure 7 As shown in the figure, the magnetic bead purification solution purified by m-PGMA-TETA50 is similar to the standard solution, while the untreated spiked extract containing complex rice matrix is ​​quite different from the standard solution, indicating that the matrix has a strong influence on As determination, and m-PGMA-TETA50 has the ability to reduce the interference of rice matrix.

[0088] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A purification magnetic bead, characterized in that: The purification magnetic beads have magnetic Fe3O4 particles as the core, and use polymerization reaction to form an epoxy-encapsulated shell, on which multiple amino adsorption groups are evenly grafted; The polyamino adsorption groups are formed by constructing amino functional compounds, and the amino functional compounds are selected from one or more of triethylenetetramine, hexamethylenediamine, and polyethyleneimine oligomers with a molecular weight of less than 1000.

2. The purification magnetic beads according to claim 1, characterized in that The shell is a polymer layer obtained by cross-linking polymerization of monomers, additives and cross-linking agents under the action of an initiator; Preferably, the monomer is selected from glycidyl methacrylate, the additive is selected from polyvinyl pyrrolidone, the crosslinking agent is selected from ethylene glycol dimethacrylate, and the initiator is selected from one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate, ammonium persulfate, potassium persulfate, benzoyl peroxide and tert-butyl benzoyl peroxide.

3. The purification magnetic beads according to claim 2, characterized in that The molar ratio of glycidyl methacrylate, polyvinyl pyrrolidone, Fe3O4 particles and ethylene glycol dimethacrylate is 1:0.4:0.2-1:0.12-0.2; The molar ratio of glycidyl methacrylate to azobisisobutyronitrile is 20-50:

1.

4. The method for preparing the purification magnetic beads according to any one of claims 1 to 3, characterized in that: The steps include: In a protective atmosphere, monomers, additives, crosslinking agents and Fe3O4 particles are mixed and crosslinked and polymerized under the action of an initiator. After the reaction is completed, the magnetic microspheres are washed and dried to obtain magnetic microspheres. The amino functional compound solution is added to the magnetic microspheres, and the reaction is carried out at 60-80° C. for 6-24 hours to obtain the purification magnetic beads.

5. The preparation method according to claim 4, characterized in that: The concentration of the amino functional compound solution is 1-100wt%, preferably 40-70wt%, and the dispersing solvent used is selected from one of water, a mixture of ethanol and water, tetrahydrofuran, and N,N-dimethylformamide.

6. The preparation method according to claim 4, characterized in that: The reaction temperature of the cross-linking polymerization reaction is 60-80°C, and the reaction time is 6-24h.

7. Use of the purification magnetic beads as described in any one of claims 1 to 3 in heavy metal detection of grains.

8. A method for electrochemically detecting arsenic content in rice, characterized in that: Adsorbing metal ions and food matrix in rice extract by using the purification magnetic beads as described in any one of claims 1 to 3, fixing the purification magnetic beads with an external magnetic field, taking the supernatant, and detecting the arsenic content in the purified rice extract; The metal ions are selected from at least one of Cu, Cd, Pb, Al, V, Cr, Co, Ni, Zn, Ga, Se, Ag, In, and U.

9. The use according to claim 8, characterized in that: The adsorption rate of the purification magnetic beads on arsenic in the rice extract is below 5%, preferably below 3%.

10. The use according to claim 8, characterized in that: The solid-to-liquid ratio of the purification magnetic beads to the rice extract is 1-5 mg / mL, preferably 5 mg / mL.

Citation Information

Patent Citations

  • Application of carboxyl magnetic beads in enrichment and removal of heavy metal in cereals

    CN110411812A

  • A polystyrene-divinylbenzene modified magnetic carbon nanotube composite material and its application

    CN112457456B

  • A magnetically branched polyethyleneimine for treating copper ions in wastewater and its application

    CN115090274B

  • A magnetic adsorption material and its preparation method and application

    CN116371378B